1909 Idaho Sess. Laws 6 - (:unkn) unknown (My University, 1909)
An Act To Regulate the Use and Carrying of Concealed Deadly Weapons and to Regulate the Sale or Delivery of Deadly Weapons to Minors Under the Age of Sixteen Years to Provide a Penalty for the Violation of the Provisions of this Act, and to Exempt Certain Persons, § 1: Prohibited the carrying a concealed dirk, Bowie knife, dagger, slungshot, pistol, revolver, gun, or any other deadly or dangerous weapon in any public setting.
Keywords: CARRY - CONCEALED